2018
DOI: 10.1111/imj.13752
|View full text |Cite
|
Sign up to set email alerts
|

Clinical features and outcome of patients with cutaneous melioidosis during a nosocomial outbreak in a temperate region of Australia

Abstract: Six cases of cutaneous melioidosis from southwestern Australia, a non-endemic region occurred as a result of Burkholderia pseudomallei contamination of normal saline that was used for irrigating superficial wounds. Treatment with parenteral meropenem, given by continuous infusion for 2 weeks, followed by oral antibiotics was successful in all cases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 15 publications
0
3
0
Order By: Relevance
“…It is also plausible that wearing open footwear, increased water exposure together with changes in environmental conditions during summer might also lead to increased rates of LLC caused by gram‐negative organisms such as Burkholderia pseudomallei. However, in WA the proportion of total LLC cases caused by these pathogens is likely to be very low …”
Section: Discussionmentioning
confidence: 99%
“…It is also plausible that wearing open footwear, increased water exposure together with changes in environmental conditions during summer might also lead to increased rates of LLC caused by gram‐negative organisms such as Burkholderia pseudomallei. However, in WA the proportion of total LLC cases caused by these pathogens is likely to be very low …”
Section: Discussionmentioning
confidence: 99%
“…An Australian report details the largest nosocomial melioidosis outbreak to date, secondary to contaminated saline and associated with soft tissue infections. All 6 cases developed superficial infection that resolved with parenteral and oral antimicrobial therapy (478). Cutaneous manifestations of melioidosis appear to be common in relation to contaminated medical or cleaning products (362,478,479).…”
Section: Clinical Presentationmentioning
confidence: 99%
“…16 However, a large American study of MI patients by Grubbs et al showed that length of stay and in-hospital mortality were not higher in LEP patients when adjusted for receipt of cardiac catheterisation or surgery. 17 STEMI care is much more streamlined than care of non-ST elevation ACS and our study only included those undergoing PCI which may explain the similarity between our results and those of Grubbs et al 17 Streamlining of STEMI management with PCI and the use of clinical pathways with a checklist approach, such as those used across our health network, is likely to be an important contributor in ensuring that equal care is provided to all patients regardless of English-speaking capacity. Implementing similar care pathways in other areas of cardiology and healthcare in general may help to ensure LEP patients are not disadvantaged in their care.…”
Section: Brief Communicationsmentioning
confidence: 60%